2023
DOI: 10.1007/s10803-023-05910-1
|View full text |Cite
|
Sign up to set email alerts
|

The Well-being and Support Needs of Australian Caregivers of Neurodiverse Children

Abstract: Caregivers of children with neurodiverse needs are known to experience challenges and hardship due to the increased needs of the child and the lack of support available. This study aimed to explore the support needs and well-being of caregivers of children with neurodiverse needs in Australia. Sixty-six caregivers participated in an online survey asking questions about support needs. The results highlighted five main themes that caregivers commonly experienced including: barriers to community engagement, impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…While less than 10% of caregivers reported prior use of these interventions, nearly 50% of caregivers stated that they would like access to these interventions if they were made available. These findings build on those of D'Arcy et al (2023), where caregivers reported difficulties in accessing caregiver‐focused supports. In light of evidence supporting the efficacy of caregiver training and education programs for decreasing caregiver stress (Frantz et al, 2018; Ruane et al, 2019), future work should prioritize ways to increase awareness of and access to caregiver‐focused interventions when children present for developmental assessments, in an effort to address this unmet need.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…While less than 10% of caregivers reported prior use of these interventions, nearly 50% of caregivers stated that they would like access to these interventions if they were made available. These findings build on those of D'Arcy et al (2023), where caregivers reported difficulties in accessing caregiver‐focused supports. In light of evidence supporting the efficacy of caregiver training and education programs for decreasing caregiver stress (Frantz et al, 2018; Ruane et al, 2019), future work should prioritize ways to increase awareness of and access to caregiver‐focused interventions when children present for developmental assessments, in an effort to address this unmet need.…”
Section: Discussionsupporting
confidence: 86%
“…There is evidence that caregiver‐focused interventions, including behavioral and psychoeducational therapy, parental training and education programs, and carer respite can decrease caregiver stress and improve caregiver self‐efficacy and self‐regulation (Frantz et al, 2018; Ruane et al, 2019). Despite this, caregivers of children with neurodevelopmental conditions report difficulties in accessing caregiver‐focused supports and interventions (D'Arcy et al, 2023). In addition, caregiver‐based programs and mental health supports are not currently covered under insurance schemes like the NDIS (Snow & Donnelly, 2018), further limiting access to these services.…”
Section: Introductionmentioning
confidence: 99%
“…Further, primary caregivers of Autistic children have described the time needed to research community supports, manage their child's funding, and learn how best to meet their child's needs as a part-or full-time workload, restricting their time available for other important tasks (Davy et al, 2023). Unmet support needs amongst these caregivers have been identified previously, particularly for parents with multiple children accessing funding and supports or families with little caregiving relief (D'Arcy et al, 2023;Davy et al, 2023). Thus, improving supports and resources for caregivers of Autistic children is needed to strengthen their knowledge and to assist them in navigating the different community supports and/or funding available, and to help strengthen their sense of efficacy in supporting their child's needs.…”
Section: Discussionmentioning
confidence: 98%